2000
DOI: 10.1021/jf000135o
|View full text |Cite
|
Sign up to set email alerts
|

Triterpene Alcohol and Sterol Ferulates from Rice Bran and Their Anti-inflammatory Effects

Abstract: Six novel feruloyl esters of triterpene alcohols and sterols, viz., two trans-ferulates, cycloeucalenol and 24-methylenecholesterol trans-ferulates, and four cis-ferulates, cycloartenol, 24-methyelenecycloartanol, 24-methylcholesterol, and sitosterol cis-ferulates, besides five known trans-ferulates, cycloartenol (CAR), 24-methylenecycloartanol (24-MCA), 24-methylcholesterol, sitosterol, and stigmastanol trans-ferulates, and one known cis-ferulate, stigmastanol cis-ferulate, were isolated from the methanol ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
201
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 288 publications
(211 citation statements)
references
References 23 publications
8
201
1
1
Order By: Relevance
“…These phytochemicals are α, β, γ, δ-tocopherol, tocotrienols (vitamin E) [56,57] and γ-oryzanol [56,58]. Vitamin E protects the cell membrane by preventing the oxidation of unsaturated fatty acids and by scavenging free radicals [59,60].…”
Section: Et Al 2011 Rice Branmentioning
confidence: 99%
See 1 more Smart Citation
“…These phytochemicals are α, β, γ, δ-tocopherol, tocotrienols (vitamin E) [56,57] and γ-oryzanol [56,58]. Vitamin E protects the cell membrane by preventing the oxidation of unsaturated fatty acids and by scavenging free radicals [59,60].…”
Section: Et Al 2011 Rice Branmentioning
confidence: 99%
“…Gamma-oryzanol, is present at 13 to 20 times (w/w) higher content in rice bran compared to total tocopherols and tocotrienols [133] and has been shown to decrease animal serum-cholesterol levels and antiinflammatory activities while inhibiting cholesterol oxidation in vitro [134,58,61].…”
Section: Gamma-oryzanolmentioning
confidence: 99%
“…It is reported to have antioxidant, antimicrobial, anti-inflammatory, cholesterol-lowering and anticancer activities, as well as ability to prevent thrombosis and atherosclerosis (Wilson et al 2007;Akihisa et al 2000;Ou et al 1999;Kayahara et al 1999;Mori et al 1999). Being capable of absorbing UV radiations, FA is finding place as a photoprotective constituent in many skin lotions and sunscreens (Saija et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Rice bran obtained from different varieties of pigmented rice and non-pigmented rice have antioxidant compounds such as tocotrienol, tocopherol, oryzanol, sterols, polyphenols, etc., that help in preventing the damage of body tissue and oxidative damage to DNA caused by free radicals (Nagendra Prasad et al 2011). Among these, gamma-oryzanol is not only a potent antioxidant (Xu et al 2001) but also an effective cholesterol lowering (Raghuram et al 1989) and anti-inflammatory agent (Akihisa et al 2000). Min et al (2012) reported that red and purple bran rices had significantly higher total phenolic and flavonoid concentrations and antioxidant capacities than lightcoloured bran or other cereals,and they attribute it to their higher levels of proanthocyanidins and anthocyanins, respectively.…”
Section: Introductionmentioning
confidence: 99%